Phenotyping Mouse Pulmonary Function In Vivo with the Lung Diffusing Capacity - Limjunyawong, Nathachit (J Vis Exp, 2015)
The mouse is now the primary animal used to model a variety of lung diseases. To study the mechanisms that underlie such pathologies, phenotypic methods are needed that can quantify the pathologic changes. Furthermore, to provide translational relevance to the mouse models, such measurements should be tests that can easily be done in both humans and mice. Unfortunately, in the present literature few phenotypic measurements of lung function have direct application to humans. One exception is the diffusing capacity for carbon monoxide, which is a measurement that is routinely done in humans. In the present report, we describe a means to quickly and simply measure this diffusing capacity in mice. The procedure involves brief lung inflation with tracer gases in an anesthetized mouse, followed by a 1 min gas analysis time. We have tested the ability of this method to detect several lung pathologies, including emphysema, fibrosis, acute lung injury, and influenza and fungal lung infections, as well as monitoring lung maturation in young pups. Results show significant decreases in all the lung pathologies, as well as an increase in the diffusing capacity with lung maturation. This measurement of lung diffusing capacity thus provides a pulmonary function test that has broad application with its ability to detect phenotypic structural changes with most of the existing pathologic lung models.